Laryngeal precursor lesions: Interrater and intrarater reliability of histopathological assessment. (4th May 2018) - Mehlum, Camilla Slot; Larsen, Stine Rosenkilde; Kiss, Katalin; Groentved, Aagot Moeller; Kjaergaard, Thomas; Möller, Sören; Godballe, Christian
Abstract : Objective: The World Health Organization classification (WHOC) 2017 of low‐grade versus high‐grade laryngeal dysplasia recently replaced the previous WHOC 2005 of mild, moderate, and severe dysplasia and carcinoma in situ. Our objectives were to compare the interrater agreement of the WHOC 2017 with that of the WHOC 2005 and to test the intra‐rater agreement of the WHOC 2005. Methods: Two expert head and neck pathologists rated 211 tissue samples that were initially diagnosed with laryngeal precursor lesions. The samples were rated twice according to the WHOC 2005 and once according to the WHOC 2017; estimates of interrater and intrarater agreements were calculated with kappa statistics. Results: The crude intrarater agreements using the WHOC 2005 were 0.93 for rater 1 and 0.62 for rater 2. The corresponding unweighted kappa values were 0.90 (95% confidence interval [CI], 0.86–0.95) for rater 1 and 0.43 (95% CI, 0.35–0.54) for rater 2, whereas the standard linear weighted kappa values were 0.93 (95% CI, 0.90–0.97) for rater 1 and 0.60 (95% CI, 0.53–0.69) for rater 2. The crude interrater agreement for the WHOC 2005 was 0.57, with a corresponding unweighted kappa value 0.38 (95% CI, 0.31–0.48) and a standard linear weighted kappa value 0.52 (95% CI, 0.42–0.60). The crude interrater agreement for the WHOC 2017 was 0.83, with a corresponding unweighted kappa value 0.45 (95% CI, 0.31–0.59) and a standard linear weighted kappa value 0.46 (95% CI, 0.30–0.60). Conclusion: Our results indicate difficulties in providing reliable diagnosis of laryngeal precursor lesions, even with experienced head and neck pathologists and the application of a newly revised classification system. Level of Evidence: 4. Laryngoscope, 128:2375–2379, 2018